2005
DOI: 10.1007/s10921-005-8783-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Piezoresistivity Calibration for Eddy Current Nondestructive Residual Stress Measurements

Abstract: It has been recently demonstrated [M. P. Blodgett and P. B. Nagy, J. Nondestruct. Eval. 23, 107 (2004)] that eddy current conductivity measurements can be exploited for near-surface residual stress assessment in surface-treated nickel-base superalloy components. To quantitatively assess the prevailing residual stress from eddy current conductivity measurements, the piezoresistivity coefficients of the material must be first determined using known external applied stresses. These calibration measurements are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 18 publications
0
25
1
Order By: Relevance
“…Eddy current (EC) method has been studied regarding its potential for measuring subsurface and surface residual stress based on the empirical piezoresistivity effect [2][3][4][5][6]. It has been reported that shot peening-induced change in conductivity measured using the EC method is affected by the microstructure of the material [5,[7][8].The objective of this study is to understand how the microstructure of the samples affect the eddy current measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy current (EC) method has been studied regarding its potential for measuring subsurface and surface residual stress based on the empirical piezoresistivity effect [2][3][4][5][6]. It has been reported that shot peening-induced change in conductivity measured using the EC method is affected by the microstructure of the material [5,[7][8].The objective of this study is to understand how the microstructure of the samples affect the eddy current measurements.…”
Section: Introductionmentioning
confidence: 99%
“…It is based on the well-known piezo-resistive effect, which is the linear relationship between conductivity and elastic stress. The success of this method on certain Nickel-base superalloys such as IN100 and Waspaloy is attributed to the rare feature that both the parallel and normal piezo-resistive coefficients are negative [4]. The main limitation for Eddy current spectroscopy is the lack of selectivity as surface treatment not only induces subsurface residual stress but also cold work that is difficult to separate.…”
Section: Introductionmentioning
confidence: 99%
“…Eddy current has been identified as a leading candidate for nondestructive characterization of residual stresses in engine components, particularly in nickel-base superalloys [2]. Correlations between EC signals and residual stresses in shot-peened alloys have been reported, and were attributed to the piezoresistivity effect, which refers to stress-induced changes in electrical conductivity [3,4]. Despite the significant potential of EC, several challenges have been identified against development of the measurement technique for residual stress characterization.…”
Section: Introductionmentioning
confidence: 99%